(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Drugs prescription pattern is very important at outpatient department in the tertiary care hospital. Objective: The purpose of the present study was to evaluate the distribution of patients and antibiotic prescribing trends in OPD of a Tertiary Medical College hospital. Methodology: This cross-sectional study was undertaken in the medicine, surgery, gynaecology & obstetrics and paediatrics Out Patient Department of Shaheed Suhrawardy Medical college hospital, Dhaka. The duration of the study period was 5 weeks (25th March, 2017 to 29th April, 2017). The study was designed to obtain information regarding prescribing pattern of drugs by physicians and also to analyze basal information of the prescription. The prescription were observed from the hospital’s OPD and few prescriptions were from each unit. Results: A total 320 prescription were observed from the hospital’s OPD where 80 prescriptions were from each unit. The mean age of the patients was 24.50±14.976 years. The most commonly prescribed antibiotics at medicine OPD was Cephalosporin which was 19(51.4%) cases followed by others antibiotics and azithromycin which was 9(24.3%) cases and 8(21.6%) cases respectively. In surgery OPD, the most commonly used antibiotics were flucloxacillin and cephalosporin which was 66(82.5%) cases and 24(30.0%) cases respectively. In Gynae & obstetrics OPD, the most commonly prescribed antibiotics were quinolones as well as other groups of antibiotics which were 23(46.0%) cases and 27(54.0%) cases respectively. Conclusion: In conclusion most commonly used antibiotic are Cephalosporin, azithromycin and Flucloxacillin in different OPD of the hospital. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):54-58